Developing Synergies Between Social Entrepreneurship and Urban Planning. Evidence from Six European Cities. - Angelidou, Margarita; Mora, Luca (Taylor & Francis, 2020)
For more than two decades, entrepreneurship has been promoted as an effective means to advance the aims of urban development. Social entrepreneurship, more specifically, is seen as a driver of urban innovation and experimentation at the local level. Nevertheless, in-depth research about the opportunities that arise from the coordination of urban planning with social entrepreneurship policy at the local level is lacking. Inspired by this realisation, the research presented in this paper investigates six European cities (Terrassa, Spain; Göteborg, Sweden; Torino, Italy; Lisbon, Portugal; Porto, Portugal; and Hengelo, the Netherlands) that have adopted a coordinated approach to promote social entrepreneurship in their territory. We identify the developmental benefits sought by these cities in promoting social entrepreneurship, the ways in which urban planning supports social entrepreneurship policy and vice versa, and the key challenges that cities face in pursing this. We conclude that the coordination of urban planning with social entrepreneurship policy is an emergent, interdisciplinary field with high growth potential given the current socio-economic challenges facing cities. However, the lack of awareness, expertise, actionable data and formal processes stand in the way of realising this potential.
Keywords: Stadtentwicklung; Unternehmen; Partizipation; Stadtplanung; Synergieeffekt; Entwicklungspotenzial; Social entrepreneurship; Sozialunternehmertum